Suggested activities in geometry using manipulative materials for socially-alienated children (grade four) - Fuentes, Maria B. (1973)
The purpose of this paper was to present the use of manipulative aids in teaching geometrical concepts to the socially-alienated grade four children. The study took geometry as a unit of study to illustrate the feasibility and impact of these materials to children's learning. The problem set forth by this paper was approached through integrative research.